Mental and Physical Well-Being Following Admission to Pediatric Intensive Care. Issue 5 (June 2015) - Als, Lorraine C.; Picouto, Maria D.; Hau, Sau-Ming; Nadel, Simon; Cooper, Mehrengise; Pierce, Christine M.; Kramer, Tami; Garralda, M. Elena
Abstract : Objective: To assess mental and physical well-being in school-aged children following admission to pediatric intensive care and to examine risk factors for worse outcome. Design: A prospective cohort study. Setting: Two PICUs. Subjects: A consecutive sample of 88 patients 5–16 years old (median age, 10.00 yr; interquartile range, 6.00–13.00 yr) admitted to PICU from 2007 to 2010 with septic illness, meningoencephalitis, or other critical illnesses were assessed a median of 5 months following discharge and outcomes compared with 100 healthy controls. Interventions: None. Measurements and Main Results: Parents completed questionnaires documenting child mental and physical well-being, including the Strengths and Difficulties Questionnaires, Chalder Fatigue Scale, and Child Sleep Habits Questionnaire. Children over 8 years completed the Impact of Event Scale -8. The children admitted to PICU scored worse on all measures in comparison with the healthy controls, with 20% scoring at risk for psychiatric disorder, 34% with high levels of post-traumatic stress symptoms, 38% at risk for fatigue disorder, and 80% scoring at risk for sleep disturbance. In the PICU group, multivariable regression analyses identified septic illness as an independent predictor of post-traumatic stress symptoms and family status, past child health problems, and PICU length of stay as predictors of reduced general mental well-being. Conclusions: Our findings indicate that a significant minority of school-aged children admitted to PICU are at risk for reduced mental and physical well-being in the short term. Symptoms of poor mental well-being were linked to both vulnerability factors and critical illness factors.